Pengaruh Pembelajaran Berbasis Masalah dan Penemuan Terbimbing Terhadap Keterampilan Proses Sains Siswa SMA Negeri 1 Langsa - Roza, Cut Badzlina; Hasruddin, Hasruddin; Edi, Syahmi (Jurnal Pendidikan Biologi, 2016)
This research aimed to determine the effect of learning model on: science process skills in SMA Negeri 1 Langsa. The research applied experimental queasy method research with 3 classes which were using by cluster randome technique. Class A learnt with problem based learning model, class B withÂ  guided discovery lerning model, while class C (control) learnt with conventional lerning model. the data analysis technique used Covariat Analysis (ANACOVA) at the level of significance Î± = 0,05 by using SPSS 21.0. The result showed: there was significant effect of learning models on studentâs science process skill (F = 50.953; P = 0.00). studentâs science process skill learnt by problem based learning (84.5 Â± 5.3) significantly higher than guided discovery (75.30 Â± 7.7), and conventional learning models (65.90 Â± 8.1).